2015
DOI: 10.1097/md.0000000000001356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dual Time Point Imaging 18F-FDG PET/CT in Differentiating Malignancy From Benign Gastric Disease

Abstract: To assess the clinical value of dual time point imaging (DTPI) fluorine-18fludeoxyglucose (18F-FDG) positron emission tomography (PET)/CT in differentiating malignancy and benign disease of patients with focally increased gastric uptake.Patients who present focally increased 18F-FDG uptake in gastric wall on conventional PET/CT imaging received delayed imaging. PET/CT scans were acquired at 1 and 2 hours (early and delayed imaging) after 18F-FDG injection. The maximum standardized uptake value (SUV) was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
4
0
2
Order By: Relevance
“…Further improvement of sensitivity, overall accuracy and AUC in the delayed 18 F-FDG PET/CT images to 86.7 %, 80 %, and 0.800 (95 % CI, 0.65–0.94, p = 0.0003) when the retention parameter ΔSUVmax>0 was used for analysis, and to 93.3 %, 80 %, and 0.833 (95 % CI, 0.61–0.92, p = 0.0001) when localized uptake pattern was used for analysis. Again, Cui et al reported that the sensitivity and AUC had significant improvement to 86.7 % and 0.873 (95 % CI, 0.786–0.961) in delayed images; which is similar to our findings [ 14 ]. Also, our findings were concordant with those reported by Xu et al who studied the value of DTP 18 F-FDG PET/CT in differentiation of malignant from benign gastrointestinal diseases and found significantly higher accuracy of DTP 18 F-FDG PET/CT imaging than that of single-time point 18 F-FDG PET/CT imaging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further improvement of sensitivity, overall accuracy and AUC in the delayed 18 F-FDG PET/CT images to 86.7 %, 80 %, and 0.800 (95 % CI, 0.65–0.94, p = 0.0003) when the retention parameter ΔSUVmax>0 was used for analysis, and to 93.3 %, 80 %, and 0.833 (95 % CI, 0.61–0.92, p = 0.0001) when localized uptake pattern was used for analysis. Again, Cui et al reported that the sensitivity and AUC had significant improvement to 86.7 % and 0.873 (95 % CI, 0.786–0.961) in delayed images; which is similar to our findings [ 14 ]. Also, our findings were concordant with those reported by Xu et al who studied the value of DTP 18 F-FDG PET/CT in differentiation of malignant from benign gastrointestinal diseases and found significantly higher accuracy of DTP 18 F-FDG PET/CT imaging than that of single-time point 18 F-FDG PET/CT imaging.…”
Section: Discussionsupporting
confidence: 92%
“…Cui et al studied the value of DTP 18 F-FDG PET/CT imaging following water drinking in differentiating malignancy from benign gastric disease and reported sensitivity, specificity, and AUC of 65.2 %, 64.3 % and 0.635 (95 % CI 0.507–0.764) respectively on early imaging, which is comparable to our findings, but they reported numerous benign cases had increased 18 F-FDG uptake indistinguishable from that of malignancy; and again they did not find an acceptable SUVmax cut-off value on early imaging [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
“…Peu d'é tudes ont exploré l'inté rêt du DTP dans le bilan des né oplasies gastriques [90][91][92]. Dans une sé rie de 74 patients, Cui et al ont ré alisé une seconde acquisition d'images 120 min aprè s l'injection du 18 F-FDG lorsqu'un hypermé tabolisme focal é tait observé au niveau de la paroi gastrique aprè s 60 min et ont ainsi montré que la SUVmax tardive, mais plus encore la diffé rence de SUV entre les deux temps d'examen, permettaient de distinguer une pathologie bé nigne d'une maligne [92]. Pour distinguer la malignité de l'hypermé tabolisme gastrique, un RI supé rieur à 13 % pré sentait une sensibilité de 87 %, une spé cificité de 89 % et une AUC de 0,92.…”
Section: Cancers Digestifsunclassified
“…Pour l'identification du caractè re malin des lé sions primitives de la tête et du cou, les ré sultats sont discordants quant à la plusvalue d'une acquisition DTP par rapport à une acquisition classique [11,76,78], tout comme dans les tumeurs de l'oesophage [87,88] et des voies biliaires [118,119], alors que la seule é tude ré alisé e sur les lé sions gastriques montre une amé lioration des sensibilité et spé cificité par rapport à l'acquisition classique [92]. Dans les tumeurs du pancré as, les ré sultats montrent le plus souvent une amé lioration des performances de la TEP au 18 F-FDG acquise en DTP pour identifier les lé sions malignes en comparaison à l'acquisition classique, mais pas de maniè re unanime [94,97,98,100].…”
Section: Caracte´risation Malin/be´ninunclassified
“…Takahashi et al [ 11 ] evaluated the pattern of 18 F-FDG uptake in the stomach in association with endoscopic findings of the gastric mucosa in 272 cases and found that accumulation pattern of 18 F-FDG largely corresponds to the presence of mucosal inflammation. Although semi-quantitative evaluation of 18 F-FDG uptake using standardized uptake values (SUVs) in the stomach has been used for assessing MALT lymphoma [ 12 ], differentiating malignant and benign gastric diseases [ 13 ] and predicting the prognosis of gastric carcinoma [ 14 ], the value of SUV measurement of FDG uptake for detecting H. pylori infection and subsequent chronic atrophic gastritis has not been well established. Lin et al [ 15 ] found a significant positive correlation between SUVs of 18 F-FDG in the stomach and the values of C-13 urea breath test which is the most commonly used noninvasive test for H. pylori .…”
Section: Introductionmentioning
confidence: 99%